Respuesta :
2x+y=7
-x+y =1 --> y = 1+x
Substitution y -->
2x+1+x=7;
3x+1=7;
3x=6;
x=2
y=1+2=3
x=2, y=3
-x+y =1 --> y = 1+x
Substitution y -->
2x+1+x=7;
3x+1=7;
3x=6;
x=2
y=1+2=3
x=2, y=3
2x + y = 7 ---> ( 1st equation )
-x + y = 1 ---> ( 2nd equation)
Let's solve this problem by substitution method
So let's set 2nd equation to y equals
-x + y = 1 ---> ( 2nd equation)
adding x on both sides
y = 1 + x ---> (3rd Equation )
Substituting the value of y in equation 1
2x + x + 1 = 7
subtracting 1 from both sides
2x + x = 6
adding like terms on the left side
3x = 6
dividing both sides by 3
x = 2
Substituting the value of x in 2nd equation
-x + y = 1
-2 + y = 1
adding 2 on both sides
y = 1 + 2
y = 3
So, our answer is x = 2
y = 3
To check the answer pick any equation and substitute the values of x and y check check if it is equal to Right hand side
2(2) + 3 = 7 ( substituting in 1st equation)
4 + 3 = 7
7 = 7
-2 + 3 = 1 ( substituting in 2nd equation)
1 = 1
Hence proved.
Hope this helps you. :D
-x + y = 1 ---> ( 2nd equation)
Let's solve this problem by substitution method
So let's set 2nd equation to y equals
-x + y = 1 ---> ( 2nd equation)
adding x on both sides
y = 1 + x ---> (3rd Equation )
Substituting the value of y in equation 1
2x + x + 1 = 7
subtracting 1 from both sides
2x + x = 6
adding like terms on the left side
3x = 6
dividing both sides by 3
x = 2
Substituting the value of x in 2nd equation
-x + y = 1
-2 + y = 1
adding 2 on both sides
y = 1 + 2
y = 3
So, our answer is x = 2
y = 3
To check the answer pick any equation and substitute the values of x and y check check if it is equal to Right hand side
2(2) + 3 = 7 ( substituting in 1st equation)
4 + 3 = 7
7 = 7
-2 + 3 = 1 ( substituting in 2nd equation)
1 = 1
Hence proved.
Hope this helps you. :D